Indian Federalism in the New Millennium - Dua, B.D.,; Singh, M.P., (Brill | Manohar Publishers & Distributors, 2024)
The Indian federal system has been dynamic in accommodating political and societal changes since its constitutional blueprint was drawn in 1949-50. However, there has been a fundamental transformation in the operative principles of federalism particularly during the last decade or so. The rhythm and the beat of the political system, and of the federal system within it, has changed on account of a variety of socio-economic and political factors, but primarily because of a disarray of the party system, neo-liberal economic policies, and judicial decisions. The centralizing thrust of the earlier years has yielded to some kind of a 'confederal' operation of the political system, making the formulation and implementation of public policies a 'consociational' exercise between political elites at the two levels of government-central and provincial-with the third, now constitutionally entrenched level-local institutions of self-government-waiting in the wings. The eighteen papers in this volume, written by experts in the field, reflect on the new and emerging trends in Indian federalism in particular and in the Indian political system in general in the larger context of global and regional changes.